4-Azidobenzyl ferrocenylcarbamate as an anticancer prodrug activated under reductive conditions - Kinski, Elisa; Marzenell, Paul; Hofer, Walter; Hagen, Helen; Raskatov, Jevgenij A.; Knaup, Karl; Zolnhofer, Eva; Meyer, Karsten; Mokhir, Andriy (Journal of Inorganic Biochemistry, 2016)
Aminoferrocene-based prodrugs are activated in the presence of cancer-specific amounts of reactive oxygen species, e.g. H2O2, with the formation of products of two types: Fe-containing complexes, which catalyze generation of HO and O2-, and quinone methides, which alkylate glutathione and inhibit the antioxidative system of the cell. Both processes act synergistically by increasing the oxidative stress in cancer cells thereby leading to their death. However, in the activation step including the cleavage of a B-C bond one molecule of H2O2 is consumed that counteracts the desired effect of the products released from aminoferrocenes. We replaced an H2O2-sensitive trigger in original prodrugs with an azide group. This trigger is slowly reduced in the presence of glutathione with the formation of an unstable arylamine intermediate, which decomposes with the release of iron ions and iminoquinone methides. These products induce strong oxidative stress in cells as we confirmed using 2′,7′-dichlorodihydrofluorescin diacetate reagent in combination with flow cytometry. In this case the activation process does not consume H2O2. Correspondingly, we observed that the azide-containing prodrug is substantially more toxic towards human promyelocytic leukemia cell line HL-60 (IC50 = 27 ± 4 μM) than its H2O2-responsive analogue (IC50 > 50 μM).
CRIS-Team Scopus Importer:2020-09-14
Keywords: Azide; Cancer; Ferrocene; Prodrug; Reduction

An intermediate cobalt(IV) nitrido complex and its N-migratory insertion product. - Zolnhofer, Eva; Käß, Martina; Khusniyarov, Marat; Heinemann, Frank Wilhelm; Maron, Laurent; Van Gastel, Maurice; Bill, Eckhard; Meyer, Karsten (Journal of the American Chemical Society, 2014)
Low-temperature photolysis experiments (T = 10 K) on the tripodal azido complex [(BIMPN(Mes,Ad,Me))Co(II)(N3)] (1) were monitored by EPR spectroscopy and support the formation of an exceedingly reactive, high-valent Co nitrido species [(BIMPN(Mes,Ad,Me))Co(IV)(N)] (2). Density functional theory calculations suggest a low-spin d(5), S = 1/2, electronic configuration of the central cobalt ion in 2 and, thus, are in line with the formulation of complex 2 as a genuine, low-spin Co(IV) nitride species. Although the reactivity of this species precludes handling above 50 K or isolation in the solid state, the N-migratory insertion product [(NH-BIMPN(Mes,Ad,Me))Co(II)](BPh4) (3) is isolable and was reproducibly synthesized as well as fully characterized, including CHN elemental analysis, paramagnetic (1)H NMR, IR, UV-vis, and EPR spectroscopy as well as SQUID magnetization and single-crystal X-ray crystallography studies. A computational analysis of the reaction pathway 2 → 3 indicates that the reaction readily occurs via N-migratory insertion into the Co-C bond (activation barrier of 2.2 kcal mol(-1)). In addition to the unusual reactivity of the nitride 2, the resulting divalent cobalt complex 3 is a rare example of a trigonal pyramidal complex with four different donor ligands of a tetradentate chelate-an N-heterocyclic carbene, a phenolate, an imine, and an amine-binding to a high-spin Co(II) ion. This renders complex 3 chiral-at-metal.

Assigning Electronic States in Carbon Nanodots - Strauß, Volker; Kahnt, Axel; Zolnhofer, Eva; Meyer, Karsten; Maid, Harald; Placht, Christian; Bauer, Walter; Nacken, Thomas; Peukert, Wolfgang; Etschel, Sebastian; Halik, Marcus; Guldi, Dirk Michael (Advanced Functional Materials, 2016)
Luminescent carbon nanodots exhibit enormous potential to be used as functional building blocks in energy conversion devices. Their intrinsic heterogeneity, however, hinders a thorough characterization and subsequently their applicability. In this work, the spectroscopic and electrochemical properties of prototype carbon nanodots were thoroughly studied in solution. Spectro-electrochemical experiments revealed information on the spectral features of several oxidized and reduced species of our carbon nanodots. Therefore, these experiments were complemented with pulse radiolysis where the spectral signature of the one-electron oxidized and reduced forms were identified. Both, electrochemically and radiolytically reduced and oxidized products show high reactivity in solution which correlates with an open-shell character, detected by paramagnetic resonance spectroscopy. The herein presented studies help to understand the complex nature of carbon nanodots and serve to overcome difficulties in device fabrication.

A Stable Crystalline Triarylphosphine Oxide Radical Anion - Schaub, Tobias; Zolnhofer, Eva; Halter, Dominik; Shubina, Tatyana; Hampel, Frank; Meyer, Karsten; Kivala, Milan (Angewandte Chemie International Edition, 2016)
Triarylphosphine oxides (Ar3P=O) are being intensely studied as electron-accepting (n-type) materials. Despite the widespread application of these compounds as electron conductors, experimental data regarding the structural and electronic properties of their negatively charged states remain scarce owing to their propensity for follow-up chemistry. Herein, a carefully designed triarylphosphine oxide scaffold is disclosed that comprises sterically demanding spirofluorenyl moieties to shield the central phosphoryl (P=O) moiety. This compound undergoes chemical one-electron reduction to afford an exceptionally stable radical anion, which was isolated and characterized by X-ray crystallography for the very first time. The experimental data, corroborated by computational studies, shall allow for the construction of phosphine oxide materials with enhanced stability.
EAM Import::2019-03-13

Cationic Two-Coordinate Complexes of Pd(I) and Pt(I) Have Longer Metal-Ligand Bonds Than Their Neutral Counterparts - Macinnis, Morgan C.; Demott, Jessica C.; Zolnhofer, Eva; Zhou, Jia; Meyer, Karsten; Hughes, Russell P.; Ozerov, Oleg V. (Chem, 2016)
One-electron oxidation of known (tBu3P)2M (1, M = Pd; 2, M = Pt) with [Ph3C][HCB11Cl11] leads to two-coordinate, monovalent cations of the formula [(tBu3P)2M][HCB11Cl11] (3, M = Pd; 4, M = Pt), which also possess linear geometry but with elongated M–P bonds. Spectroscopic and computational studies consistently show that the unpaired electron of the d9 configuration of 3 and 4 belongs to largely non-bonding orbitals: the s/dz2 hybrid for Pd and the degenerate dx2-y2/dxy pair for Pt. We show that molecular-orbital-based arguments alone are incapable of predicting or rationalizing the observed M–P bond lengthening on oxidation; correct prediction and rationalization are achieved only by inclusion of electrostatic and Pauli effects. This emphasizes the dangers of interpreting any perturbative changes in bond metrics solely on the basis of energies and occupancies of molecular orbitals; the inclusion of electrostatic and Pauli components is essential to providing a more complete picture.
EAM Import::2019-03-13

Configurationally Stable Chiral Dithia-Bridged Hetero[4]helicene Radical Cation: Electronic Structure and Absolute Configuration - Gliemann, Bettina; Petrovic, Ana G.; Zolnhofer, Eva; Dral, Pavlo O.; Hampel, Frank; Breitenbruch, Georg; Schulze, Philipp; Raghavan, Vijay; Meyer, Karsten; Polavarapu, Prasad L.; Berova, Nina; Kivala, Milan (Chemistry - An Asian Journal, 2017)
A stable chiral hetero[4]helicene radical cation was synthesized and characterized by UV/Vis absorption and EPR spectroscopy, as well as X-ray crystallography. For the first time, a combination of chiroptical methods involving ECD, ORD, and VCD, supported by quantum mechanical predictions, enabled the elucidation of the absolute configuration of such open-shell helical species.
EAM Import::2019-03-13

Cyclo-P3 Complexes of Vanadium: Redox Properties and Origin of the 31P NMR Chemical Shift - Pinter, Balazs; Smith, Kyle T.; Kamitani, Masahiro; Zolnhofer, Eva; Tran, Ba L.; Fortier, Skye; Pink, Maren; Wu, Gang; Manor, Brian C.; Meyer, Karsten; Baik, Mu-Hyun; Mindiola, Daniel J. (Journal of the American Chemical Society, 2015)
The synthesis and characterization of two high-valent vanadium-cyclo-P3 complexes, (nacnac)V(cyclo-P3)(Ntolyl2) (1) and (nacnac)V(cyclo-P3)(OAr) (2), and an inverted sandwich derivative, [(nacnac)V(Ntolyl2)]2(2-3:2-cyclo-P3) (3), are presented. These novel complexes are prepared by activating white phosphorus (P4) with three-coordinate vanadium(II) precursors. Structural metrics, redox behavior, and DFT electronic structure analysis indicate that a [cyclo-P3]3- ligand is bound to a V(V) center in monomeric species 1 and 2. A salient feature of these new cyclo-P3 complexes is their significantly downfield shifted (by 300 ppm) 31P NMR resonances, which is highly unusual compared to related complexes such as (Ar[iPr]N)3Mo(cyclo-P3) (4) and other cyclo-P3 complexes that display significantly upfield shifted resonances. This NMR spectroscopic signature was thus far thought to be a diagnostic property for the cyclo-P3 ligand related to its acute endocyclic angle. Using DFT calculations, we scrutinized and conceptualized the origin of the unusual chemical shifts seen in this new class of complexes. Our analysis provides an intuitive rational paradigm for understanding the experimental 31P NMR spectroscopic signature by relating the nuclear magnetic shielding with the electronic structure of the molecule, especially with the characteristics of metal-cyclo-P3 bonding.
CRIS-Team Scopus Importer:2020-09-14

Electronic Structure and Magnetic Properties of a Low-Spin CrIIComplex: Trans-[CrCl2(dmpe)2] (dmpe = 1,2-Bis(dimethylphosphino)ethane) - Zolnhofer, Eva; Opalade, Adedamola A.; Jackson, Timothy A.; Heinemann, Frank Wilhelm; Meyer, Karsten; Krzystek, J.; Ozarowski, Andrew; Telser, Joshua (Inorganic Chemistry, 2021)
Octahedral coordination complexes of the general formula trans-[MX2(R2ECH2CH2ER2)2] (MII = Ti, V, Cr, Mn; E = N, P; R = alkyl, aryl) are a cornerstone of both coordination and organometallic chemistry, and many of these complexes are known to have unique electronic structures that have been incompletely examined. The trans-[CrCl2(dmpe)2] complex (dmpe = Me2PCH2CH2PMe2), originally reported by Girolami and co-workers in 1985, is a rare example of a six-coordinate d4 system with an S = 1 (spin triplet) ground state, as opposed to the high-spin (S = 2, spin quintet) state. The ground-state properties of S = 1 systems are challenging to study using conventional spectroscopic methods, and consequently, the electronic structure of trans-[CrCl2(dmpe)2] has remained largely unexplored. In this present work, we have employed high-frequency and -field electron paramagnetic resonance (HFEPR) spectroscopy to characterize the ground-state electronic structure of trans-[CrCl2(dmpe)2]. This analysis yielded a complete set of spin Hamiltonian parameters for this S = 1 complex: D = +7.39(1) cm-1, E = +0.093(1) (E/D = 0.012), and g = [1.999(5), 2.00(1), 2.00(1)]. To develop a detailed electronic structure description for trans-[CrCl2(dmpe)2], we employed both classical ligand-field theory and quantum chemical theory (QCT) calculations, which considered all quintet, triplet, and singlet ligand-field states. While the high density of states suggests an unexpectedly complex electronic structure for this "simple"coordination complex, both the ligand-field and QCT methods were able to reproduce the experimental spin Hamiltonian parameters quite nicely. The QCT computations were also used as a basis for assigning the electronic absorption spectrum of trans-[CrCl2(dmpe)2] in toluene.
CRIS-Team Scopus Importer:2021-11-26

Electronic Structure and Magnetic Properties of a Titanium(II) Coordination Complex - Zolnhofer, Eva; Wijeratne, Gayan B.; Jackson, Timothy A.; Fortier, Skye; Heinemann, Frank Wilhelm; Meyer, Karsten; Krzystek, J.; Ozarowski, Andrew; Mindiola, Daniel J.; Telser, Joshua (Inorganic Chemistry, 2020)
Stable coordination complexes of TiII (3d2) are relatively uncommon, but are of interest as synthons for low oxidation state titanium complexes for application as potential catalysts and reagents for organic synthesis. Specifically, high-spin TiII ions supported by redox-inactive ligands are still quite rare due to the reducing power of this soft ion. Among such TiII complexes is trans-[TiCl2(tmeda)2], where tmeda = N,N,N′,N′-tetramethylethane-1,2-diamine. This complex was first reported by Gambarotta and co-workers almost 30 years ago, but it was not spectroscopically characterized and theoretical investigation by quantum chemical theory (QCT) was not feasible at that time. As part of our interest in low oxidation state early transition metal complexes, we have revisited this complex and report a modified synthesis and a low temperature (100 K) crystal structure that differs slightly from that originally reported at ambient temperature. We have used magnetometry, high-frequency and -field EPR (HFEPR), and variable-temperature variable-field magnetic circular dichroism (VTVH-MCD) spectroscopies to characterize trans-[TiCl2(tmeda)2]. These techniques yield the following S = 1 spin Hamiltonian parameters for the complex: D = -5.23(1) cm-1, E = -0.88(1) cm-1, (E/D = 0.17), g = [1.86(1), 1.94(2), 1.77(1)]. This information, in combination with electronic transitions from MCD, was used as input for both classical ligand-field theory (LFT) and detailed QCT studies, the latter including both density functional theory (DFT) and ab initio methods. These computational methods are seldom applied to paramagnetic early transition metal complexes, particularly those with S > 1/2. Our studies provide a complete picture of the electronic structure of this complex that can be put into context with the few other high-spin and mononuclear TiII species characterized to date.
CRIS-Team Scopus Importer:2020-05-26

Electronic Structure and Reactivity of a Well-Defined Mononuclear Complex of Ti(II) - Wijeratne, Gayan B.; Zolnhofer, Eva; Fortier, Skye; Grant, Lauren N.; Carroll, Patrick J.; Chen, Chun-Hsing; Meyer, Karsten; Krzystek, J.; Ozarowski, Andrew; Jackson, Timothy K.; Mindiola, Daniel J.; Telser, Joshua (Inorganic Chemistry, 2015)
A facile and high-yielding protocol to the known Ti(II) complex trans-[(py)4TiCl2] (py = pyridine) has been developed. Its electronic structure has been probed experimentally using magnetic susceptibility, magnetic circular dichroism, and high-frequency and high-field electron paramagnetic resonance spectroscopies in conjunction with ligand-field theory and computational methods (density functional theory and ab initio methods). These studies demonstrated that trans-[(py)4TiCl2] has a 3Eg ground state (dxy1dxz,yz1 orbital occupancy), which, as a result of spin-orbit coupling, yields a ground-state spinor doublet that is EPR active, a first excited-state doublet at ∼60 cm-1, and two next excited states at ∼120 cm-1. Reactivity studies with various unsaturated substrates are also presented in this study, which show that the Ti(II) center allows oxidative addition likely via formation of [Ti(η2-R2E2)Cl2(py)n] E = C, N intermediates. A new Ti(IV) compound, mer-[(py)3(η2-Ph2C2)TiCl2], was prepared by reaction with Ph2C2, along with the previously reported complex trans-(py)3Ti=NPh(Cl)2, from reaction with Ph2N2. Reaction with Ph2CN2 also yielded a new dinuclear Ti(IV) complex, [(py)2(Cl)2Ti(μ2:η2-N2CPh2)2Ti(Cl)2], in which the two Ti(IV) ions are inequivalently coordinated. Reaction with cyclooctatetraene (COT) yielded a new Ti(III) complex, [(py)2Ti(η8-COT)Cl], which is a rare example of a mononuclear "piano-stool" titanium complex. The complex trans-[(py)4TiCl2] has thus been shown to be synthetically accessible, have an interesting electronic structure, and be reactive toward oxidation chemistry.
CRIS-Team Scopus Importer:2020-09-14

Electronic Structure of trans-[VIICl2(E(CH3)2CH2CH2E(CH3)2)2], E=N, P - Jafari, Mehrafshan G.; Zolnhofer, Eva; Fehn, Dominik; Heinemann, Frank Wilhelm; Opalade, Adedamola A.; Carroll, Patrick J.; Meyer, Karsten; Krzystek, J.; Ozarowski, Andrew; Mindiola, Daniel J.; Jackson, Timothy A.; Telser, Joshua (European Journal of Inorganic Chemistry, 2024)
Coordination complexes of general formula trans-[MX2(R2ECH2CH2ER2)2] (MII=Ti, V, Cr, Mn; E=N or P; R=alkyl or aryl) are a cornerstone of coordination and organometallic chemistry. We investigate the electronic properties of two such complexes, trans-[VCl2(tmeda)2] and trans-[VCl2(dmpe)2], which thus represent trans-[MX2(R2ECH2CH2ER2)2] where M=V, X=Cl, R=Me and E=N (tmeda) and P (dmpe). These VII complexes have S=3/2 ground states, as expected for octahedral d3. Their tetragonal distortion leads to zero-field splitting (zfs) that is modest in magnitude (D≈0.3 cm−1) relative to analogous S=1 TiII and CrII complexes. This parameter was determined from conventional EPR spectroscopy, but more effectively from high-frequency and -field EPR (HFEPR) that determined the sign of D as negative for the diamine complex, but positive for the diphosphine, which information had not been known for any trans-[VX2(R2ECH2CH2ER2)2] systems. The ligand-field parameters of trans-[VCl2(tmeda)2] and trans-[VCl2(dmpe)2] are obtained using both classical theory and ab initio quantum chemical theory. The results shed light not only on the electronic structure of VII in this environment, but also on differences between N and P donor ligands, a key comparison in coordination chemistry.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Diamines; Diphosphines; EPR; Ligand-field theory; Quantum chemistry

From an Fe2P3 complex to FeP nanoparticles as efficient electrocatalysts for water-splitting - Yao, Shenglai; Forstner, Viktoria; Menezes, Prashanth W.; Panda, Chakadola; Mebs, Stefan; Zolnhofer, Eva; Miehlich, Matthias; Szilvasi, Tibor; Kumar, Nanjundan Ashok; Haumann, Michael; Meyer, Karsten; Grutzmacher, Hansjorg; et al. (Chemical Science, 2018)
In large-scale, hydrogen production from water-splitting represents the most promising solution for a clean, recyclable, and low-cost energy source. The realization of viable technological solutions requires suitable efficient electrochemical catalysts with low overpotentials and long-term stability for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) based on cheap and nontoxic materials. Herein, we present a unique molecular approach to monodispersed, ultra-small, and superiorly active iron phosphide (FeP) electrocatalysts for bifunctional OER, HER, and overall water-splitting. They result from transformation of a molecular iron phosphide precursor, containing a [Fe2P3] core with mixed-valence FeIIFeIII sites bridged by an asymmetric cyclo-P(2+1) 3- ligand. The as-synthesized FeP nanoparticles act as long-lasting electrocatalysts for OER and HER with low overpotential and high current densities that render them one of the best-performing electrocatalysts hitherto known. The fabricated alkaline electrolyzer delivered low cell voltage with durability over weeks, representing an attractive catalyst for large-scale water-splitting technologies.
CRIS-Team Scopus Importer:2020-09-14

Hydrogenated Anatase: Strong Photocatalytic Dihydrogen Evolution without the Use of a Co-Catalyst - Liu, Ning; Schneider, Christopher; Freitag, Detlef; Venkatesan, Uma Maheswari; Marthala, Venkata; Hartmann, Martin; Winter, Benjamin; Spiecker, Erdmann; Osvet, Andres; Zolnhofer, Eva; Meyer, Karsten; Nakajima, Tomohiko; et al. (Angewandte Chemie International Edition, 2014)
The high-pressure hydrogenation of commercially available anatase or anatase/rutile TiO2 powder can create a photocatalyst for H-2 evolution that is highly effective and stable without the need for any additional co-catalyst. This activation effect cannot be observed for rutile; however, for anatase/rutile mixtures, a strong synergistic effect can be found (similar to results commonly observed for noble-metal-decorated TiO2). EPR and PL measurements indicated the intrinsic co-catalytic activation of anatase TiO2 to be due to specific defect centers formed during hydrogenation. These active centers can be observed specifically for high-pressure hydrogenation; other common reduction treatments do not result in this effect.
Keywords: co-catalyst; hydrogenation; titanium(III); TiO2; water splitting

Influence of the nacnac Ligand in Iron(I)-Mediated P4 Transformations - Spitzer, Fabian; Grassl, Christian; Balazs, Gabor; Zolnhofer, Eva; Meyer, Karsten; Scheer, Manfred (Angewandte Chemie International Edition, 2016)
A study of P4 transformations at low-valent iron is presented using β-diketiminato (L) FeI complexes [LFe(tol)] (tol=toluene; L=L1 (1 a), L2 (1 b), L3 (1 c)) with different combinations of aromatic and backbone substituents at the ligand. The products [(LFe)4(μ4-η2:η2:η2:η2-P8)] (L=L1 (2 a), L2 (2 b)) containing a P8 core were obtained by the reaction of 1 a,b with P4 in toluene at room temperature. Using a slightly more sterically encumbered ligand in 1 c results in the formation of [(L3Fe)2(μ-η4:η4-P4)] (2 c), possessing a cyclo-P4 moiety. Compounds 2 a-c were comprehensively characterized and their electronic structures investigated by SQUID magnetization and 57Fe Mössbauer spectroscopy as well as by DFT methods.
CRIS-Team Scopus Importer:2020-09-14
Keywords: Mössbauer spectroscopy; paramagnetic compounds; small-molecule activation; substituent effects; white phosphorus

Metal-Ligand Cooperativity Promoting Sulfur Atom Transfer in Ferrous Complexes and Isolation of a Sulfurmethylenephosphorane Adduct - Sorsche, Dieter; Miehlich, Matthias; Zolnhofer, Eva; Carroll, Patrick J.; Meyer, Karsten; Mindiola, Daniel J. (Inorganic Chemistry, 2018)
The reaction of elemental sulfur with the cis-divacant octahedral complex [(pyrr2py)Fe(OEt2)] (1; pyrr2py2- = 3,5-tBu2-bis(pyrrolyl)pyridine) yields the iron dimer [(pyrr-1-S-pyrrpy)Fe]2 (2; pyrr-1-S-pyrrpy2- = 3,5-(tBu2-pyrrolyl)(1-S-3,5-tBu2-pyrrolyl)pyridine) resulting from a pyrr2py2- ligand based S-oxidation of one pyrrole arm. Addition of the phosphorus ylide H2CPPh3 to 1 forms the ylide adduct [(pyrr2py)Fe(CH2PPh3)] (3), which upon reaction with elemental sulfur produces a rare example of a sulfurmethylenephosphorane adduct, [(pyrr2py)Fe(SCH2PPh3)] (4). The sulfur-oxidized pyrrole group of the ligand pyrr-1-S-pyrrpy2- can be reversed, since complex 2 exhibits S atom transferability via the addition of 2 equiv of H2CPPh3 to yield a mixture of compounds 3 and 4. For all complexes reported, the ferrous ion remains S = 2. Complexes 2-4 were characterized by single-crystal X-ray diffraction as well as 1H NMR spectroscopy, solid and solution magnetic studies, and 57Fe Mössbauer spectroscopic measurements.
CRIS-Team Scopus Importer:2020-09-14

Nacnac-Cobalt-Mediated P4Transformations - Spitzer, Fabian; Grassl, Christian; Balazs, Gabor; Maedl, Eric; Keilwerth, Martin; Zolnhofer, Eva; Meyer, Karsten; Scheer, Manfred (Chemistry - A European Journal, 2017)
A comparison of P4activations mediated by low-valent β-diketiminato (L) cobalt complexes is presented. The formal Co0source [K2(L3Co)2(μ2:η1,η1-N2)] (1) reacts with P4to form a mixture of the monoanionic complexes [K(thf)6][(L3Co)2(μ2:η4,η4-P4)] (2) and [K(thf)6][(L3Co)2(μ2:η3,η3-P3)] (3). The analogue CoIprecursor [L3Co(tol)] (4 a), however, selectively yields the corresponding neutral derivative [(L3Co)2(μ2:η4,η4-P4)] (5 a). Compound 5 a undergoes thermal P atom loss to form the unprecedented complex [(L3Co)2(μ2:η3,η3-P3)] (6). The products 2 and 3 can be obtained selectively by an one-electron reduction of their neutral precursors 5 a and 6, respectively. The electrochemical behaviour of 2, 3, 5 a, and 6 is monitored by cyclic voltammetry and their magnetism is examined by SQUID measurements and the Evans method. The initial CoI-mediated P4activation is not influenced by applying the structurally different ligands L1and L2, which is proven by the formation of the isostructural products [(LCo)2(μ2:η4,η4-P4)] [L=L3(5 a), L1(5 b), L2(5 c)].
CRIS-Team Scopus Importer:2020-09-14
Keywords: cyclic voltammetry; paramagnetic NMR; small molecule activation; white phosphorus; β-diketiminates

Noble-Metal-Free Photocatalytic H2Generation: Active and Inactive ‘Black’ TiO2Nanotubes and Synergistic Effects - Liu, Ning; Schneider, Christopher; Freitag, Detlef; Zolnhofer, Eva; Meyer, Karsten; Schmuki, Patrik (Chemistry - A European Journal, 2016)
Over the past five years a number of different synthesis approaches has been reported to obtain so-called ‘black’ titania. One of the outstanding features of the material is that certain synthesis processes lead to the formation of an intrinsic co-catalytic center and thus enable noble-metal free photocatalytic H2-generation. In the present work, using TiO2nanotube layers, we compare three common ‘blackening’ approaches, namely i) the original high-pressure hydrogenation (HPT-H2), ii) a classic high temperature reduction in Ar, and iii) an electrochemical (cathodic) reduction. We demonstrate that except for high pressure hydrogenation also cathodic reduction leads to an activation of TiO2- that is, it exhibits noble-metal-free photocatalytic H2generation. Moreover, we show that a combination of cathodic reduction/high pressure hydrogenation leads to a synergistic effect, that is, a significant enhancement of the combined co-catalytic activity.
CRIS-Team Scopus Importer:2020-09-14
Keywords: black TiO; nanotubes; noble metal free; photocatalytic H; synergistic effects

Noble-Metal-Free Photocatalytic Hydrogen Evolution Activity: The Impact of Ball Milling Anatase Nanopowders with TiH2 - Zhou, Xuemei; Liu, Ning; Schmidt, Jochen; Kahnt, Axel; Osvet, Andres; Romeis, Stefan; Zolnhofer, Eva; Marthala, Venkata; Guldi, Dirk Michael; Peukert, Wolfgang; Hartmann, Martin; Meyer, Karsten; et al. (Advanced Materials, 2016)
Ball milling TiO2 anatase together with TiH2 can create an effective photocatalyst. The process changes the lattice and electronic structure of anatase. Lattice deformation created by mechanical impact combined with hydride incorporation yield electronic gap-states close to the conduction band of anatase. These provide longer lifetimes of photogenerated charge carriers and lead to an intrinsic cocatalytic activation of anatase for H2 evolution.
Keywords: Anatase; Ball milling; Hydrogen evolution; Photocatalysis; Titanium hydride

Stable Co-Catalyst-Free Photocatalytic H 2 Evolution From Oxidized Titanium Nitride Nanopowders - Zhou, Xuemei; Zolnhofer, Eva; Nguyen, Nhat Truong; Liu, Ning; Meyer, Karsten; Schmuki, Patrik (Angewandte Chemie, 2015)
A simple strategy is used to thermally oxidize TiN nanopowder (∼20nm) to an anatase phase of a TiO2:Ti3+:N compound. In contrast to the rutile phase of such a compound, this photocatalyst provides activity for hydrogen evolution under AM1.5 conditions, without the use of any noble metal co-catalyst. Moreover the photocatalyst is active and stable over extended periods of time (tested for 4months). Importantly, to achieve successful conversion to the active anatase polymorph, sufficiently small starting particles of TiN are needed. The key factor for catalysis is the stabilization of the co-catalytically active Ti3+ species against oxidation by nitrogen present in the starting material.
EAM Import::2019-03-13

Synthesis and characterization of divalent manganese, iron, and cobalt complexes in tripodal phenolate/N-heterocyclic carbene ligand environments - Käß, Martina; Hohenberger, Johannes; Adelhardt, Mario; Zolnhofer, Eva; Mossin, Susanne; Heinemann, Frank Wilhelm; Sutter, Jörg; Meyer, Karsten (Inorganic Chemistry, 2014)
Two novel tripodal ligands, (BIMPN) and (MIMPN), combining two types of donor atoms, namely, NHC and phenolate donors, were synthesized to complete the series of N-anchored ligands, ranging from chelating species with tris(carbene) to tris(phenolate) chelating arms. The complete ligand series offers a convenient way of tuning the electronic and steric environment around the metal center, thus, allowing for control of the complex's reactivity. This series of divalent complexes of Mn, Fe, and Co was synthesized and characterized by H NMR, IR, and UV/vis spectroscopy as well as by single-crystal X-ray diffraction studies. Variable-temperature SQUID magnetization measurements in the range from 2 to 300 K confirmed high-spin ground states for all divalent complexes and revealed a trend of increasing zero-field splitting |D| from Mn(II), to Fe(II), to Co(II) complexes. Zero-field Fe Mössbauer spectroscopy of the Fe(II) complexes 3, 4, 8, and 11 shows isomer shifts δ that increase gradually as carbenes are substituted for phenolates in the series of ligands. From the single-crystal structure determinations of the complexes, the different steric demand of the ligands is evident. Particularly, the molecular structure of 1 - in which a pyridine molecule is situated next to the Mn-Cl bond - and those of azide complexes 2, 4, and 6 demonstrate the flexibility of these mixed-ligand derivatives, which, in contrast to the corresponding symmetrical TIMEN ligands, allow for side access of, e.g., organic substrates, to the reactive metal center. © 2013 American Chemical Society.

TiO2 Nanotubes: Nitrogen-Ion Implantation at Low Dose Provides Noble-Metal-Free Photocatalytic H-2-Evolution Activity - Zhou, Xuemei; Häublein, Volker; Liu, Ning; Nguyen, Nhat Truong; Zolnhofer, Eva; Tsuchiya, Hiroaki; Manuela, Killian; Meyer, Karsten; Schmuki, Patrik; Frey, Lothar (Angewandte Chemie International Edition, 2016)
Low-dose nitrogen implantation induces an ion and damage profile in TiO2 nanotubes that leads to co-catalytic activity for photocatalytic H-2-evolution (without the use of any noble metal). Ion implantation with adequate parameters creates this active zone limited to the top part of the tubes. The coupling of this top layer and the underlying non-implanted part of the nanotubes additionally contributes to an efficient carrier separation and thus to a significantly enhanced H-2 generatio
Keywords: H-2 evolution; ion implantation; nitrogen; photocatalysis; TiO2 nanotubes

Transfer Reagent for Bonding Isomers of Iron Complexes - Schmidt, Monika; Seitz, Andreas E.; Eckhardt, Maria; Balazs, Gabor; Peresypkina, Eugenia V.; Virovets, Alexander V.; Riedlberger, Felix; Bodensteiner, Michael; Zolnhofer, Eva; Meyer, Karsten; Scheer, Manfred (Journal of the American Chemical Society, 2017)
The cothermolysis of As4 and [Cp″2Zr(CO)2] (Cp″ = η5-C5H3tBu2) results in the formation of [Cp″2Zr(η1:1-As4)] (1) in high yields and the arsenic-rich complex [(Cp″2Zr)(Cp″Zr)(μ, η2:2:1-As5)] (2) as a minor product. In contrast to yellow arsenic, 1 is a light-stable, weighable and storable arsenic source for subsequent reactions. The transfer reaction of 1 with [Cp'Fe(μ-Br)]2 (Cp' = η5-C5H2tBu3) yields the unprecedented bond isomeric complexes [(Cp'Fe)2(μ, η4:4-As4)] (3a) and [(Cp'Fe)2(μ, η4:4-cyclo-As4)] (3b). In contrast, the analogous reaction with the CpBn derivative [CpBnFe(μ-Br)]2 (CpBn = η5-C5(CH2(C6H5)5) leads exclusively to the triple decker complex [(CpBnFe)2(μ, η4:4-As4)] (4) possessing the tetraarsabutadiene-type ligand analogous to 3a. To elucidate the stability of the bonding isomers 3a and 3b, DFT calculations were performed. The oxidation of 4 with AgBF4 affords [(CpBnFe)2(μ, η5:5-As5)][BF4] (5), which is a product expanded by one arsenic atom, instead of the expected complex [(CpBnFe)2(μ, η4:4-cyclo-As4)]+.
CRIS-Team Scopus Importer:2020-09-14

Unique anisotropic optical properties of a highly stable metal-organic framework based on trinuclear iron(iii) secondary building units linked by tetracarboxylic linkers with an anthracene core - Vinogradov, A. V.; Milichko, V. A.; Zaake-Hertling, H.; Aleksovska, A.; Gruschinski, S.; Schmorl, S.; Kersting, B.; Zolnhofer, Eva; Sutter, Jörg; Meyer, Karsten; Lönnecke, P.; Hey-Hawkins, Evamarie (Dalton Transactions, 2016)

Unusual Dinitrogen Binding and Electron Storage in Dinuclear Iron Complexes - Sorsche, Dieter; Miehlich, Matthias; Searles, Keith; Gouget, Guillaume; Zolnhofer, Eva; Fortier, Skye; Chen, Chun Hsing; Gau, Michael; Carroll, Patrick J.; Murray, Christopher B.; Caulton, Kenneth G.; Khusniyarov, Marat; et al. (Journal of the American Chemical Society, 2020)
A rare example of a dinuclear iron core with a non-linearly bridged dinitrogen ligand is reported in this work. One-electron reduction of [(tBupyrr2py)Fe(OEt2)] (1) (tBupyrr2py2- = 2,6-bis((3,5-di-tert-butyl)pyrrol-2-yl)pyridine) with KC8 yields the complex [K]2[(tBupyrr2py)Fe]2(μ2-η·1:η·1-N2) (2), where the unusual cis-divacant octahedral coordination geometry about each iron and the η·5-cation-πcoordination of two potassium ions with four pyrrolyl units of the ligand cause distortion of the bridging end-on μ-N2 about the FeN2Fe core. Attempts to generate a Et2O-free version of 1 resulted instead in a dinuclear helical dimer, [(tBupyrr2py)Fe]2 (3), via bridging of the pyridine moieties of the ligand. Reduction of 3 by two electrons under N2 does not break up the dimer, nor does it result in formation of 2 but instead formation of the ate-complex [K(OEt2)]2[(tBupyrr2py)Fe]2 (4). Reduction of 1 by two electrons and in the presence of crown-ether forms the tetraanionic N2 complex [K2][K(18-crown-6)]2(tBupyrr2py)Fe]2(μ2-η·1:η·1-N2) (5), also having a distorted FeN2Fe moiety akin to 2. Complex 2 is thermally unstable and loses N2, disproportionating to Fe nanoparticles among other products. A combination of single-crystal X-ray diffraction studies, solution and solid-state magnetic studies, and 57Fe Mössbauer spectroscopy has been applied to characterize complexes 2-5, whereas DFT studies have been used to help explain the bonding and electronic structure in these unique diiron-N2 complexes 2 and 5.
CRIS-Team Scopus Importer:2020-06-02